PENERAPAN HUKUM ISLAM DI ACEH TAMIANG: BERDAMAI DENGAN SYARIAT DALAM PLURALITAS SANKSI KHALWAT - Fakhrurrazi dan; Budi Juliandi (IAIN Ambon, 2017)
This study explained that Qanun No. 9/2008 of 18 cases were resolved through “village justice” or in accordance with adat (one of which was the case of khalwat) indicated that there wasn’t an explicit command of Aceh government to people in handing over the offence Qanun No. 14/2003 of khalwat to court (Mahkamah Syariah). In addition, Qanun No. 9/2008 indicated that Aceh government could do nothing to resolve the offences like khalwat through court (Mahkamah Syariah). The fact that there was no single (plural) jurisdictional authority encouraged people in looking for favorable rules. The number of khalwat offences weren’t resolved by Mahkamah Syariah by the cane (cambuk), but through traditional institutions by a variety of fine custom, asserting such this assumption. This study asserted Daniel S Lev’s point of view that Islamic law was never been accepted by unanimous anywhere. Islamic law was often modified to suit the local values, accepted, and regarded as Islamic law which derived its validity from the scholars or religious authority. This study also asserted the institutional theory of Gresham which said that a formal process tended to be avoided in order to resolve the dispute through a process which is more family-oriented and more accommodating. This study also criticized the opinion of Alyasa Abu Bakr said, that the completion of seclusion cases through traditional mechanisms will strengthen the enforcement of Islamic law. Instead, this paper put forward the argument that the resolution of these cases through traditional mechanisms seclusion will weaken the enforcement of Islamic law. Keywords: legal pluralism, fine custom, cane, khalwat